Vladimir Nabokov’s Self-Translated Lolita: Revisiting the Original Alliterative Modes - Cechanovičius, Artūras; Krūminienė, Jadvyga (Respectus Philologicus, 2012)
This paper is a case study comparison of Vladimir Nabokov’s self-translated Russian version of his English novel Lolita with its original text within the frame of the theory of literary translation. Here, self-translation is referred to as a branch of literary translation whose distinctive feature is that the work is both composed and translated by the same person. It is interesting to observe that, for the most part, the authors who translate their own works into another language are bilingual. Theoretical investigation into the field of self-translation is a recent endeavour; the term only appeared around 1976. Before it appeared in A Dictionary for the Analysis of Literary Translation, self-translation was thought to be related to bilingualism, and was therefore approached from the perspective of linguistics. This paper analyses some alliterative modes, including suballiteration, produced by Nabokov in the two versions of Lolita. Throughout, the process of translation is viewed as a “two-stage reading-writing activity.” The novel’s translation into Lithuanian, which was performed from Nabokov’s Russian translation, is used to show the difference between translation and selftranslation, and to reveal the clash or the interplay between the foreign and the domestic in the development of alliterative appeal.